Pengembangan Framework Yii Dalam Pembangunan Sistem Inventaris STMIK Prabumulih Dengan Konsep User Centered Design (UCD) - Ariansyah Ariansyah; Ahmat Josi (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
STMIK Prabumulih is a college that has two departments, namely the department of the information system level of education (S1) and computerized accounting level of diploma three (D3). STMIK Prabumulih has a vision of "Becoming a high school based on information technology with a national standard in 2025". For the achievement of the vision, STMIK Prabumulih has implemented an IT system, such as Academic System, Alumni Database System, eLearning, Learning System. This research aimed to develop an Equipment Management System as a complimentary from another established system. The Equipment Management System intended to make an efficient equipment management handling like an inventory system.